2010
DOI: 10.1007/s12028-010-9393-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine Infusion for Blood Pressure Control in Patients with Subarachnoid Hemorrhage

Abstract: In this study, nicardipine infusion was a safe and moderately effective treatment for BP control in patients with SAH. Although SBP during nicardipine infusion was higher than the pre-specified goal in a significant percentage of hourly observations, this may be due to the drug administration protocol and other factors such as analgesia and sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…[17] Systolic blood pressures were controlled below 180 mmHg by administering calcium antagonists nicardipine. [31] Nimodipine was not used (this drug is unavailable in Japan). Fasudil hydrochloride was administered three times a day, with a dose of 30 mg at each administration.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Systolic blood pressures were controlled below 180 mmHg by administering calcium antagonists nicardipine. [31] Nimodipine was not used (this drug is unavailable in Japan). Fasudil hydrochloride was administered three times a day, with a dose of 30 mg at each administration.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Varelas et al22) reported effectiveness and safety of nicardipine infusion in reducing SBP and DBP to pre-specified goal. Nicardipine achieved SBP control in 59.9% of hourly infusion measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Qureshi et al19) reported the feasibility and safety of nicardipine use in treatment of acute hypertension with ICH, and Varelas et al22) demonstrated nicardipine infusion for controlling elevated blood pressure after SAH. However, the study showing controlling acute hypertension after SAH is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The superior parallel randomized trial was powered to demonstrate the outcome of SBP during the first hour of spontaneous ICH. According to data from previous studies, nicardipine infusion reduced the SBP to 25.1 ± 11.2 mmHg in SAH [ 21 ]. The mean ± standard deviation (SD) of SBP in patients who received nicardipine intravenous bolus followed by continuous infusion was 34 ± 8.5 mmHg [ 22 ] The hypothesis test was two-tailed with criteria for significance (α) of 0.05.…”
Section: Methodsmentioning
confidence: 99%